Habituation of Moderate Religious Values at the Ihyaul Ulum DDI Baruga Majene Islamic Boarding School - Idris, Syarifuddin; Ahmad Irvani; Syarifah HR DG Tujuh; Nihla Kamilah; Besse Ruhaya (Jurnal Sustainable, 2025)
This study discusses the habituation of religious moderation values at the Ihyaul Ulum DDI Baruga Islamic Boarding School in Majene Regency, West Sulawesi. Data collection was carried out through interviews, observation, and documentation. The results show that the leaders of the Ihyaul Ulum DDI Islamic Boarding School believe that Islam is a religion that carries a mission of compassion and Rahmatan Lil 'Alamin, providing safety and security for Muslims and others. Islam is a religion that accommodates differences and tolerance, and respects the diverse realities of religious practice while still promoting unity and integrity. The values of religious moderation that are habituated in Islamic boarding schools are: tawassut (moderation), tawazun (maintaining balance and harmony), i'tidal (straightforwardness, being fair in actions or reactions), tasamuh (tolerance), and tasyawwur (deliberation). The sources of reference are the Qur'an, Hadith, the book Akhlak Lil Banin (written by Umar Bin Ahmad Baradja), Ta'lim Muta'allim (Sheikh Az -Zurnuji), Arbain Nawawi (Imam Yahya Bin Syarifuddin An Nawawi), and Jawahirul Kalamiyah (Sheikh Thahir Bin Shalih Al Jazairy). The process of habituating the values of religious moderation for santri is carried out through various activities using the methods of habituation, direct practicing, and modeling.